An Enhanced Control Strategy for the Stable Operation of Distributed Generation during Grid-Connected and Islanded Mode - Suman Khichar; Yatindra Gopal; Mahendra Lalwani (International Journal of Applied Power Engineering (IJAPE), 2018)
The incident of islanding occurs while the distributed generator fed constant power into the grid after power flow on the source of essential utility has been intermittent. If islanding is not rapidly detected, it can reason serious security and harmful condition.  This paper presents coordinated manage of solar photovoltaic unit through maximum power point tracking technique to make available voltage and frequency support for an islanding condition. In normal condition, structure works as constant current control mode subsequent to islanding the structure switched to voltage control mode. The projected technique is capable to discriminate involving an islanding and a non-islanding occurrence. In this paper phase locked loop detection technique designed for detecting islanding situation is conceded out. The authentication of proposed system is established efficiently using MATLAB/ Simulink environment. The simulated results exhibit that the islanding detection technique has zero nondetection zone property and be able to detect islanding within few seconds